The appeal of information transactions - Antonio Cabrales; Olivier Gossner; Roberto Serrano (Brown University, Department of Economics, 2012)
An information transaction entails the purchase of information. Formally, it consists of an information structure together with a price. We develop an index of the appeal of information transactions, which is derived as a dual to the agent's preferences for information. The index of information transactions has a simple analytic characterization in terms of the relative entropy from priors to posteriors, and it also connects naturally with a recent index of riskiness.
Keywords: C00; C43; D00; D80; D81; G00; G11; 330; informativeness; information transactions; Kullback-Leibler divergence; relative entropy; decision under uncertainty; investment; Blackwell ordering